Homelessness and self-rated health: evidence from a national survey of homeless people in Spain - Fernando Fajardo-Bullón; Igor Esnaola; Isobel Anderson; Lars Benjaminsen (BMC, 2019)
Abstract Background Internationally, acute homelessness is commonly associated with complex health and social care needs. While homelessness can be understood as an outcome of structural housing exclusion requiring housing led solutions, the health care issues faced by homeless people equally require attention. A substantive evidence base on the health needs of homeless people exists, but relatively little is known about what influences the self-rated health of homeless people. This article presents new evidence on whether drug use (alcohol consumption, ever having used drugs), health variables (visiting a hospital once in the last year, visiting the doctor in the last month, having a health card, sleeping difficulties, and having a disabling impairment) and sociodemographic characteristics are significantly associated with Self-Rated Health (SRH) among Spanish homeless people. Method The approach applies secondary analysis to cross-sectional data from a sample of 2437 homeless adults in Spain (83.8% were male). Multinomial logistic regression modelling was used to analyse the relationships between drug use, other health variables and SRH. Results Being male, an abstainer, having a health card and being in the youngest age groups were significant factors associated with perceived good health. On the other hand, ever having used drugs, having been a night in hospital, having gone to the doctor in the last month, having sleeping difficulties, having a disabling impairment and being in the older age group were all significant risk factors associated with perceived poor health. Conclusions These results help to improve understanding of the key factors that influence the SRH among homeless people. The findings can contribute to development and delivery of preventive policies, suggesting that interventions to reduce drug consumption and ensure access to a health card/health services, as well as enhancing services for older, female and disabled homeless people are all measures which could improve health and well-being for those who face homelessness. Effective housing interventions (e.g. Housing First or Permanent Supported Housing programmes) are equally important to underpin the effectiveness of measures to improve the self-rated health of homeless people.